Clinical Characteristics, Treatment Outcomes, and Prognostic Factors in Hodgkin Lymphoma: A Retrospective Cohort Study at King Khalid Hospital, Najran - Badheeb, Ahmed M.; Al Greshah, Hasan Salem; Elhadi, Musadag; Alyami, Nasher H; Aman, Abdelaziz; Seada, Islam A; Abu Bakar, Abdullah; Alkarak, Samer; Bazuqamah, Mohammed S; Mohammed, Mahran; Idris, Ammar; Ahmed, Faisal; et al. (Asian Pacific Journal of Cancer Care, 2026)
Introduction: Hodgkin lymphoma (HL) is characterized by heterogeneous clinical outcomes influenced by a complex interplay of biological and clinical factors. This study aims to delineate presentation patterns, treatment responses, and prognostic indicators within a Saudi Arabian cohort, with consideration of regional epidemiological variations. Materials and Methods: A retrospective cohort study was conducted involving 23 patients diagnosed with HL at King Khalid Hospital, Najran, between 2014 and 2021. Diagnoses were established according to the World Health Organization (WHO) 2017 classification. Treatment responses were assessed after every two chemotherapy cycles using RECIST version 1.1, due to limited availability of PET imaging modalities. Progression-free survival (PFS) predictors were analyzed using univariate Cox proportional hazards regression, with explicit acknowledgment of the limited statistical precision stemming from the small sample size. Results: The mean age was 36.3 ± 16.3 years, with males constituting 60.9% of the cohort. Nodular sclerosis was the most common histological subtype (65.2%), and stage III was the most frequent at diagnosis (43.5%). The ABVD chemotherapy regimen yielded an objective response rate of 78.3%, with a complete response observed in 43.5% of patients. At a median follow-up of 33 months, univariate analysis identified significant associations between reduced PFS and advanced disease stage (III/IV vs. I/II; hazard ratio [HR] 3.26, 95% confidence interval [CI] 0.34–31.35; p=0.001), high International Prognostic Score (IPS ≥3 vs. 0–2; HR 17.93, 95% CI 1.85–173.94; p=0.013), and increasing age (per year; HR 1.21, 95% CI 1.10–1.34; p<0.001). Conclusions: In this cohort, advanced disease stage, elevated IPS, and increasing age were associated with inferior PFS, consistent with established prognostic models despite regional epidemiological differences. These findings underscore the necessity for larger, prospective studies to validate risk stratification tools and optimize management strategies in similar healthcare settings.